Measurement of agarwood using magnetic induction mechanism - Ishak, Nurfarahin (2021)
Aquilaria malaccensis (agarwood) in Malaysia is well known as “gaharu” and is a scented tree that produces fragrant resinous wood. Agarwood is a high-value wood that has extensive uses as perfumes, incense, and medicine. Due to its economic value and high demand from the industry, agarwood has been exposed to exploitation by agarwood hunters. The usual method of obtaining agarwood is cutting down the whole tree without examining the existence of agarwood. This may lead to natural treasure loss, money loss, and species extinction. To prevent these losses, a non-destructive method is desirable to replace the usual method. Magnetic induction mechanism is introduced as a non-destructive method to detect the formation of agarwood. This technique offers a great deal to visualise the distribution of electrical impedance. Developing the elemental magnetic circuit started with obtaining the dielectric properties via the open-ended coaxial probe method. The open-ended coaxial probe method had a limited frequency of between 200 MHz and 1 GHz. Therefore, the data underwent extrapolation for the target frequency of 10 MHz. These data were used to observe the agarwood reaction in a virtual simulation. Second, a virtual magnetic induction using COMSOL simulation was constructed, with 10 MHz frequency being used as the transmission frequency. There were two main observations conducted for this simulation, which were magnetic field and induced current. In COMSOL simulation, also observed were the parameters for designing the coils. Coil diameter and coil layers gave a great impact on the performance of the magnetic field and induced current. Lastly, an elemental transceiver circuit was designed. The peak-topeak voltage was observed to see the voltage changes between the transmitter and the receiver. The magnetic induction circuit was successfully able to sense frequency changes. The voltage readings for the sample without agarwood were high (1.02 V– 1.30 V) compared with samples with agarwood formation, whose voltage readings were low (Sample A: 976 mV–1.20 V, Sample B: 940 mV–1.17 V, Sample C: 840m V–1.18 V).